(untitled) (Philologia, 2021)
The article aims to demonstrate that two 18th-century novels, Richardson’s Pamela (1740) and Burney’s Evelina (1778), were produced according to the same principle, which may be succinctly summed in Edmund Burke’s phrase: ”Beauty in distress [is] much the most affecting beauty” (Philosophical Enquiry, 1757). The narrative patterns and protagonists have a lot in common. Needless to say, both novels enjoyed tremendous popularity and success in their day, mostly with female audiences.